Faktor-Faktor yang Mempengaruhi Akuntabilitas Kinerja Instansi Pemerintah Daerah Kabupaten Ogan Komering Ulu - Reni Febrianti; Anis Feblin; Hasiatul Aini (IPM2KPE, 2019)
The purpose of this study was to determine the factors that influence the Accountability of OKU Regency Government Institution Performance. The method used in this study is non probability sampling, namely purposive sampling. The analysis technique used is multiple linear regression and hypothesis testing is a statistical test partially (t test) and simultaneous (F test). T test results show that there is a significant influence of internal control and motivation on the Performance Accountability of OKU Regency Government Agencies with a t table value of 2.00758. F test results show a sig value of 0,000 <0.05 or obtain an F value of 15.517> F table 2.40 which means that together the budget target clarity (X1), accounting control (X2), reporting system (X3), internal control (X4), and motivation (X5) have a significant effect on performance accountability. Based on the coefficient of determination obtained a value of 0.564. Conclusions, the contribution of the clarity of budget targets, accounting controls, reporting systems, internal controls, and motivation to performance accountability was 56.4%, while the remaining 43.6% was influenced by other variables not explained in this study. Keywords: Performance Accountability, Government Institutions